Penundaan Pembayaran Kewajiban Pembayaran Utang Akibat Covid-19 Yang Dikatagorikan Sebagai Force Majeur - Dianti, Faiza; Mekka Putra, Mohamad Fajri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The purpose of this study is to study and analyze further regarding the postponement of debt payment obligations due to Covid-19 which is used as an excuse as a force majeure condition. The research method used is the normative juridical method. Where this research focuses on legislation, books, and other related literature. Covid-19 has caused various negative impacts, one of which has an impact on the inability of debtors to pay their debts to creditors. This then has an impact on increasing cases of bankruptcy applications, especially requests for postponement of debt payment obligations (PKPU), debt payments are made by applicants to the respondent but the respondent does not perform according to what has been promised, achievements cannot be made due to covid-19 reasons. The research was conducted by examining the legal systematics related to legislation regarding agreements, coercive circumstances and PKPU as well as by examining library materials or secondary data in the form of various literatures and doctrines of experts regarding agreements, coercive circumstances and PKPU. Research analysis was conducted using qualitative methods. Thus, the COVID-19 pandemic can be used as an excuse by debtors in PKPU.